CD48 on blood leukocytes and in serum of asthma patients varies with severity. Issue 6 (1st December 2016) - Gangwar, R. S.; Minai‐Fleminger, Y.; Seaf, M.; Gutgold, A.; Shikotra, A.; Barber, C.; Chauhan, A.; Holgate, S.; Bradding, P.; Howarth, P.; Eliashar, R.; Berkman, N.; et al.
Abstract: Background: CD48 is a membrane receptor (mCD48) on eosinophils and mast cells and exists in a soluble form (sCD48). CD48 has a pivotal role in murine asthma and in the proinflammatory interactions of mast cells with eosinophils via its ligand CD244. Thus, CD48 might be important in human asthma. Methods: Therefore, two separate cohorts (IL and UK) comprising mild, moderate, and severe asthma and healthy volunteers were evaluated for blood leukocyte mCD48 expression and sCD48 in serum. Asthmatic bronchial biopsies were immunostained for CD48. sCD48 effect on CD244‐dependent eosinophil activation was evaluated. Results: Eosinophil mCD48 expression was significantly elevated in moderate while downregulated in severe asthma. mCD48 expression on B, T, and NK cells and monocytes in severe asthma was significantly increased. sCD48 levels were significantly higher in mild while reduced in severe asthma. sCD48 optimal cutoff values for differentiating asthma from health were identified as >1482 pg/ml (IL) and >1619 pg/ml (UK). In asthmatic bronchial biopsies, mCD48 was expressed predominantly by eosinophils. sCD48 inhibited anti‐CD244‐induced eosinophil activation. Conclusions: mCD48 and sCD48 are differentially expressed in the peripheral blood of asthma patients of varying severity. sCD48 inhibits CD244‐mediated eosinophil activation. These findings suggest that CD48 may play an important role in human asthma.